PENGARUH DOSIS POC LIMBAH KULIT PISANG TERHADAP PERTUMBUHAN DAN HASIL TANAMAN PAKCOY (Brassica rapa L) The Effect Of Organic Fertilizer Banana Rind To Growth And Yield Of Pakcoy (Brassica rapa L) - Farida; Daryono (Politeknik Pertanian Negeri Samarinda, 2017)
The effect of organic fertilizer banana rind to growth and yield of pakcoy aimed to know the effect of organicfertilizer banana rind the best to growth and yield of pakcoy.Experiment were hold in Sangatta, East Kutai on May- August 2016 period.The experiments was conducted in non factorial experiments on Completely RandominazedDesign (CRD) with fve replications. The factor is D0 = no application D1= 4 ml/plant/aplication, D2 = 6ml/plant/aplication, D3= 8 ml/plant/aplication, D4 = 10 ml/plant/aplication. The result wasD3treatment the best resultof long plant 21, 28 days after planting, andyieldare 17,08 cm, 21,16 cm and 7,20 gram.